The Effect of Hepatic Impairment on the Pharmacokinetics of Intravenously Administered Felcisetrag (TAK‐954). (31st March 2022) - Czerniak, Richard; Cieslarová, Blanka; Kupčová, Viera; Rosario, Maria; Lock, Ruth; Dong, Cheng; Dukes, George
Abstract: Felcisetrag (formerly known as TAK‐954) is a selective serotonin receptor agonist under investigation for use in patients with postoperative gastrointestinal dysfunction. The safety, tolerability, and pharmacokinetics (PK) of intravenous (i.v.) felcisetrag have been studied, but little is known about the effect of hepatic impairment on the PK of the drug. This phase 1, non‐randomized, open‐label study compared the PK of a single 60‐minute i.v. infusion of felcisetrag between healthy individuals (n = 8) and patients with moderate (n = 10) or severe (n = 7) hepatic impairment. The primary study end points were the total and free maximum observed plasma concentration of felcisetrag at the end of infusion (Cmax ), area under the concentration–time curve (AUC) from time 0 to the time of the last quantifiable concentration (AUClast ), and AUC from time 0 to infinity (AUCinf ). Concentration–time profiles of felcisetrag were similarly shaped between groups but revealed lower concentrations of total plasma felcisetrag with increasing severity of hepatic impairment, whereas concentrations of free felcisetrag increased. The ratios of AUClast and AUCinf for patients with severe hepatic impairment were up to 29.3% lower for total felcisetrag and up to 29.2% higher for free felcisetrag than found in healthy individuals ( P < .05). Infusions were well tolerated with no discontinuations, severe adverse events, or deaths during the study. Overall, the effect of hepatic impairment on exposure to felcisetrag was minimal, suggesting that dose adjustment may be unnecessary in patients with hepatic impairment.